The possibility of applying the geographic information system (GIS) to the management of hotel investment organizations: The hotels in Najaf Governorate as a case study (Eurasian Journal of History, Geography and Economics, 2023)
The current paper focuses on the possibility of using a geographic information system (GIS) to detect the locations of hotels in Najaf Governorate to provide accuracy, speed, time, and cost in providing service to visitors. The geographic information system is an advanced technology that provides several advantages to its users, whereby the locations of buildings and places can be determined, as well as providing descriptive information about each location.